2007
DOI: 10.1111/j.1540-8175.2007.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification and Prognosis in Octogenarians Undergoing Stress Echocardiographic Study

Abstract: Stress echocardiography yields incremental prognostic information in octogenarians and effectively stratifies them into low- and high-risk groups. Precise therapeutic decision making in very elderly patients should incorporate combined clinical and stress echocardiography data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…298 Exercise echocardiography in 2159 patients >70 years (mean 75 years) with known or suspected CAD showed that the change in LV wall motion score (based on a 4-point dyskinesis ranking in each of 16 segments) from rest to peak exercise was a potent independent predictor of both death and major cardiac events. 206,299 This confirmed data in a series of 335 octogenarians in whom LV wall motion score stratified patients into low-and high-risk groups with annualized event rates of 1.2% and 5.8% per year, respectively, 300 and an earlier study of patients whose mean age was 72 years. 301 Exercise radionuclide imaging has also shown prognostic utility in this age group.…”
supporting
confidence: 67%
“…298 Exercise echocardiography in 2159 patients >70 years (mean 75 years) with known or suspected CAD showed that the change in LV wall motion score (based on a 4-point dyskinesis ranking in each of 16 segments) from rest to peak exercise was a potent independent predictor of both death and major cardiac events. 206,299 This confirmed data in a series of 335 octogenarians in whom LV wall motion score stratified patients into low-and high-risk groups with annualized event rates of 1.2% and 5.8% per year, respectively, 300 and an earlier study of patients whose mean age was 72 years. 301 Exercise radionuclide imaging has also shown prognostic utility in this age group.…”
supporting
confidence: 67%
“…Prior studies of DSE in octogenarians have reported on a total of 88 (14.7% of total combined population) cardiovascular events 15 16. This is the largest study to date assessing the safety and prognostic benefits of DSE among octogenarian patients (average age 84±3.7 years) reporting on 217 (39.5%) events, which increases the evidence base 2.5-fold.…”
Section: Discussionmentioning
confidence: 82%
“…However, only recently Chaudhry et al [21] evaluated DSE ability in prognostic stratification of patients older than 80 years. Compared to our study, Chaudhry et al examined an apparently ''less ill'' population with lower mortality (16 vs 29% in our study group).…”
Section: Dse In Octogenariansmentioning
confidence: 98%